Physiology of Responses to Active and Passive Recovery Strategies After Maximal Exercise: A Study in Track and Field Athletes - Rabbani, Muhammad Azizi; Pramono, Bayu Agung; Siantoro, Gigih; Hariyanto, Agus; Azriddin, Adlina Dayana Binti (Universitas Negeri Surabaya, 2025)
Purpose: The accumulation of lactic acid in muscle cells during intense exercise can decrease muscle and blood pH, leading to weakened muscle contractions and fatigue. The purpose of this study was to determine the effect of active recovery (jogging) on reducing blood lactate levels after a 400-meter sprint in male college students. Materials and Methods: An experimental study with a randomized control group and a pretest-posttest design was used. Twenty subjects were randomly divided into two groups of 10: a treatment group with active recovery (jogging) and a control group with passive recovery (sitting). Lactate levels were measured twice: after running and after a 5-minute recovery period. Data analysis used in this study included descriptive tests, normality tests, paired-samples t-tests, and independent-samples t-tests. Result: The research results show that active recovery significantly reduces lactate levels from an average of 16.88±3.28 mMol/L to 9.97±1.28 mMol/L, whereas passive recovery reduces them only from 16.55±2.37 mMol/L to 15.63±2.08 mMol/L. The paired t-test results showed a significant difference (p < 0.05) between the two recovery methods. Conclusion: These findings indicate that active recovery is more effective in accelerating the reduction of lactic acid levels, reducing the risk of muscle fatigue, and enhancing athletes' readiness for subsequent training or competitions.